The Effectiveness of 2023 Recess Outcomes from Lima Puluh Kota Regency Regional House of Representatives Members in the Formulation of the 2025 Regional Budget - Khairispen Waldi; Edi Haskar; Nessa Fajriyana Farda (Civiliza Publishing, 2026)
Recess activities undertaken by Regional House of Representatives (DPRD) members can be followed up through the formulation of DPRD key points of thought. These key points represent an analysis of regional development issues derived from public hearing minutes and/or meetings held to gather constituent aspirations during the recess period. This study aims to assess the effectiveness of the 2023 recess outcomes from Lima Puluh Kota Regency DPRD members regarding the formulation of the 2025 Regional Budget (APBD) in accordance with Minister of Home Affairs Regulation Number 86 of 2017 as well as to identify the factors preventing these outcomes from being accommodated and realized in the 2025 APBD and to propose solutions. This research employs a descriptive approach utilizing a socio-legal (empirical-juridical) method. Data sources comprise both primary and secondary data, which were analyzed qualitatively. The findings indicate that the 2023 recess outcomes from Lima Puluh Kota Regency DPRD members were not yet effective in the context of the 2025 APBD formulation, as they failed to meet the five assessment indicators derived from Sutrisno’s program effectiveness theory. The factors preventing the accommodation and realization of these recess outcomes in the 2025 APBD include both internal and external elements. Proposed solutions involve enhancing the capacity of DPRD members through technical guidance, strengthening coordination, conducting preliminary verification of recess outcomes, ensuring all proposals are accompanied by supporting documentation, establishing a priority scale, and intensifying DPRD oversight and monitoring of verified key points of thought through to the APBD deliberation stage.